Skin-in-the-game in ABS transactions: A critical review of policy options - Jan Pieter Krahnen; Christian Wilde (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
This paper applies the theory of structured finance to the regulation of asset backed securities. We find the current regulation in Europe (Article 405 of the CRR) and the US (Section D of Dodd-Frank Act) to be severely flawed with respect to its key intention: the imposition of a strict loss retention requirement. While nominal retention is always 5%, the true level of loss retention varies across available retention options between zero loss reten- tion and full loss retention at the extreme ends. Based on a standard model of structured finance transactions, we propose a new risk retention metric RM measuring the level of an issuer's skin-in-the-game. The new metric could help to achieve a better implementation of CRR/CRD-IV and DFA, by making disclosure of the RM-number compulsory for all ABS transactions. There are also implications for the operation of rating agencies. On a general level, the RM metric will be instrumental in achieving simplicity and transparency in securitizations (STS).
urn:nbn:de:hebis:30:3-429042
Keywords: G2; 330; structured finance; ABS; STS (simple; transparent; and standardized securitizations); regulation; retention; capital; Dodd-Frank Act